BIOMASSA DAN HASIL LIMA GENOTIPE SORGUM (Sorghum bicolor [L.] Moench) DI LAHAN KERING TANJUNG BINTANG LAMPUNG SELATAN - Devy Nouva Ristiani (Inovasi Pembangunan : Jurnal Kelitbangan, 2021)
Abstract: This experiment aims to evaluate the effect of five genotypes on the biomass and yield of sorghum, to calculate correlation between biomass variables and yield components, and to calculate the coefficient of direct effect and indirect effect of biomass component on yield of grain sorghum by using path analysis. This study was conducted in Sukanegara Village, Tanjung Bintang District, South Lampung Regency, Lampung Province from April 2019 to November 2019. This study used single treatment of sorghum genotypes in Completely Randomized Block Design (CRBD) with three replications. The sorghum genotypes used that this study were (GHP-1, GHP-5, GHP-11, Pahat, and Numbu). The total number of study units was 15. In each unit of study, five plants were taken as samples of observations. The results showed that genotypes GHP-5 (135,2 g) and Pahat (123,4 g) had a higher above-ground biomass weight than genotypes GHP-1 (98,0 g) and Numbu (94,7 g). Then the genotype of Pahat had panicle length (26,2 cm), number of panicle branches (42,4 item), and head weight (65,1 g) were higher than other genotypes. Then the high grain weight was achieved by the genotype GHP-5 (37,6 g), Numbu (31,0 g), and GHP-11 (29,6 g). This experiment showed that there was a significant correlation between above-ground biomass weight and grain weight per plant (r=0,36**). Based on path analysis there was a dirrect effect of above-ground biomass weight on grain weight per plant (0,035). Than, direct effect between number of grain per plant and grain weight per plant (0,995) and 1000 grain weight and grain weight per plant (0,346). It means that number of grain per plant and 1000 grain weight is recommended to be used as selection for high yield.